GEOGRAPHICAL INFORMATION SYSTEM-BASEDMULTI-CRITERIA DECISION ANALYSIS OF POTATO CULTIVATION LAND SUITABILITY IN WELIMADA DIVISIONAL SECRETARIAT, SRI LANKA - JAYASINGHE, ADIKARIGE DON SRIYANI; WITHANAGE, NEEL CHAMINDA (Potato Journal, 2021)
The purpose of the research was to apply the GIS approach to find land suitability for potato cultivation in Welimada Divisional Secretariat (DS). The task applied GIS-MCDA and Analytical Hierarchy Process (AHP). For the suitability classification, soil, physical, and socioeconomic factors were considered. While ph and salinity were sub-criteria under the soil elevation, slope, and water availability were sub-criteria under physical factors. Road and market proximity, land use were considered as sub-criteria under socio-economic factors. Suitability classification was performed through several steps including structuring, standardizing, calculating criteria weights, assign weights for criteria, and suitability assessment. As result, 41% of the total land was moderately suitable for potato cultivation and 23% of the area was highly suitable. Only 4% of the land was classified as least suitable and 14%, 15% of the land classified as low suitable and marginal suitable area respectively. These results provide knowledge about the interaction and relationship of the criteria. So, this research can be utilized as a model for fruitful potato cultivation practices as well as, it can be taken as a guide for future land use assessment in potato growing areas, especially in Sri Lanka.